The Routledge companion to the French Revolution in world history - Forrest, Alan 1945-; Middell, Matthias 1961- (Routledge companions, 2018)
Introduction / Alan Forrest and Matthias Middell -- Section I. Global repercussions of the French Revolution -- The French Revolution in the global world of the eighteenth century / Matthias Middell -- The sister republics, or the ephemeral invention of a French Republican commonwealth / Pierre Serna -- Revolution in France, revolutions in the Caribbean / Frédéric Régent -- The French Revolution in Spanish America / Michael Zeuske -- Republic and the Muslim world: for a regenerated Mediterranean system / Rachida Tlili -- The French Revolution and the Islamic world of the Middle East and North Africa / Ian Coller -- Section II. Topics of a transnational history of the French Revolution: comparisons -- Cross-channel entanglements: 1689-1789 / Robert H. Griffiths -- Atlantic entanglements: comparing the French and American revolutions / David Andress -- Japan's Meiji Revolution: an alternative model of revolution? / Hiroshi Mitani -- Section III. Topics of a transnational history of the French Revolution: entanglements -- War and cultural transfer in Europe / Alan Forrest -- Napoleon and Europe: the legacy of the French Revolution / Annie Jourdan -- Irish revolutionaries and the French Revolution / Ultán Gillen -- British radicals and revolutionary France: historiography, history and images / Pascal Dupuy -- Section IV. Traditions of seeing and interpreting the French Revolution -- The French Revolution seen from the Terres Australes / Peter McPhee -- The evolution of the Russian discourse on the French Revolution / Alexander Tchoudinov -- Revolutionary violence of the French type and its influence on the Chinese Revolution / Gao Yi